Hubungan Intelegensi Interpersonal dengan Hasil Belajar Biologi - Misahradarsi Dongoran (Institut Agama Islam Negeri, 2022)
This study aims to determine the relationship of interpersonal intelligence with biology learning outcomes and to determine the contribution of interpersonal intelligence to biology learning outcomes, the sampling technique was carried out by total sampling, the data collection tool was a closed questionnaire. The results of the analysis of the data obtained are